HABIB RIZIQ SYIHAB, DEMOKRASI DAN POLITIK ISLAM - M. Asep Rahmatullah; Nur Halimah (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2021)
Islam has long, down-to-earth historical roots from Mecca, Medina, the Middle East, Asia Africa and Europe. Islam has ruled the world since the time of the Prophet Muhammad, Khulafaur Rashidin, Bani Abbasiyah, Ummayah, Fatimids and the Ottoman Empire. At present, the big issue of Islamic governance / Islamic leadership of the Caliphate is widely discussed by the world community, especially by the Indonesian Islamic community. From the Asian Continent, especially the Indonesian soil, the Islamic spirit that entered the world of political democracy provided a breath of fresh air for big changes. In the midst of liberalist democracy, pragmatic and oligarchic politics are increasingly mushrooming, the dynamics of Indonesian politics have experienced boredom and aridity, the phenomenon of a cleric, the great Imam Habib Riziq has colored and characterized Islamic identity, idealist values ​​and ideological Islamic politics are increasingly grounded. In fact, the Islamic Defenders Front Organization movement and the leadership of the great Imam Habib Rizieq succeeded in uniting the Indonesian Muslim community, and this is a new stream of Indonesian Islamic political movement. With the spirit of courage, the great Imam Habib Riziq continued to carry out preaching and Jihad the amar ma'ruf nahyi mungkar movement consistently (Istiqomah) in criticizing the Indonesian government under presidents Joko Widodo and Ma'ruf Amin. He was able to create a new force for the political axis of Indonesian Islam which turned differences into equations, divisions into unity, and strengthened the political identity of Indonesian Islam. The optimistic spirit instilled by a great Imam Habib Riziq has made Indonesian Muslims aware of the movement and political leadership of Islam. That Islamic politics is very important to carry out all Islamic teachings that are rahmatal lil alamin. Without the political power of Islam, Islam is lame worthless in front of its opponents. Habib Rizieq's leadership style is able to heal the hearts of Indonesian Muslims from the crisis of leadership, simplicity and exemplary. Hopefully the Indonesian people will not be disappointed again in the political map of Indonesian Islam. And the great flow of Indonesian Islamic revival is able to change the political power of Islam for the whole world. Inna fatahna laka fatham mubiena